Leadership Within the Phenomenological Structure of Teacher Creativity - Žydžiūnaitė, Vilma; Butanavičius, Valentinas; Jurgilė, Vaida; Kaminskienė, Lina (Frontiers in Education, 2022)
Few studies have investigated the relationship between teachers’ leadership and creativity, and thus far, no quantitative or qualitative studies have been undertaken focusing on teacher leadership in the context of teacher creativity and, more specifically, in the context of the phenomenological structure of teacher creativity. Thus, the study presented in this article draws attention to the phenomenological relationship between teacher creativity and leadership. The research question used as a guide for this study was as follows: What does a teacher’s leadership in the phenomenological structure of teacher creativity mean? The study aimed to describe teacher leadership as a component of the phenomenological structure of teacher creativity. Phenomenology is the study of structures of consciousness as experienced from the first-person (teacher’s) point of view. In the study, integral phenomenology as a specific approach to design was applied. Unstructured in-depth phenomenological interviews were conducted with non-art discipline teachers. This means school teachers who do not teach arts (music, dance, theatre) but other subjects such as physics, mathematics, chemistry, geography, informatics, languages, biology, communication, psychology and, etc. This article presents the results of 19 analysed interviews. Findings showed that the phenomenological structure of teacher creativity consisted of eighteen themes covering specific sub-themes; one theme represented teacher leadership, encompassing innovativeness, influence, and collegiality. The teacher leadership within the phenomenological structure of teacher creativity was related to the following themes: being curious, being brave, being in relationship, being a citizen, motivating, and opening up. It could be concluded that the complex phenomenological structure of teacher creativity proves that neither teacher creativity nor leadership are individual elements or individual competencies that are acquired separately – teacher creativity is always accompanied by teacher leadership and vice versa. Findings provide opportunities to change our conceptions of teacher leadership in relation to teacher creativity. This study shows that teacher leadership does not play a key role in her/his creativity.